Analysis of the Flow Characteristics of the Liquid Film on the Wall Surface of the Corrugated Plate Dryer Based on PSD Method: A Short Communication - Wang, Bo; Chen, Bowen; Ke, Bingzheng; Wang, Gongqing; Li, Ru; Wen, Jiming; Lu, Chuan; Tian, Ruifeng (Frontiers in Energy Research, 2020)
Corrugated plate dryer is an important steam-water separation equipment in steam generator of secondary loop of nuclear power plant. Its steam-water separation efficiency has a certain influence on economic index of nuclear power plants. It is meaningful to understand flow characteristics of liquid film on corrugated plate wall. Besides, the fluctuation of the liquid film may cause the occurrence of liquid film rupture, thus the research on the fluctuation of the liquid film on the wall of the corrugated plate is very important. This paper uses Plane laser induced fluorescence (PLIF) method to measure liquid film thickness. Curve of film thickness with time is obtained. Calculation formula of average value of liquid film thickness is given. Based on power spectral density (PSD) method, non-linear characteristics of liquid film thickness are studied. Results show that the relationship between film thickness and Reynolds number conforms to Nusselt theory. Nevertheless, the results show deviation from Nusselt as well as Karapantsios estimation. When Reynolds number is in the range of 600 to 3000 and surface roughness is 0.03, the fluctuation of the power spectrum of the liquid film thickness caused by gravity can be ignored, which provides a reference for study on steam-water separation.